Kebijakan Hukum Pidana Dalam Mengatasi dan Mencegah Tindak Pidana Berita Bohong (Hoax) - Fauziah Lubis; Muhammad Roni Pratama; Ahmad Raihan Mubarak (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Fake news, also known as Hoax, is becoming increasingly popular for us to hear and is also rife in various media. Starting from print media and online media. Fake news is false or untrue information that is fabricated or distorted from real facts. The problems we discuss in this research include: How is the Criminal Law Policy in Overcoming and Preventing Fraud News Crimes According to Current Positive Law and How Criminal Law Policies are in Overcoming and Preventing Fraud News Crimes in the Future. This research is normative research. The rules regarding fake news (Hoax) which are clearly included in the Criminal Code are contained in Article 390, while the rules regarding fake news (Hoax) contained in the law are contained in law no.11 of 2008 and law no. 1 of 1946. Renewal of Law No. 11 of 2008, namely Law No. 19 of 2016. The role of the government and society is contained in Law Number 19 of 2016 and is listed in articles 40 and article 41. Rules regarding Criminal Acts of Fake News (Hoax) in the renewal criminal law is contained in the 2019 Criminal Code Bill in Article 272. Keywords: Criminal Law Policy; Hoax; Criminal Law Reform.